PENGARUH SALES GROWTH, FIXED ASSET INTENSITY DAN KEPEMILIKAN MANAJERIAL TERHADAP TAX AVOIDANCE - Novita Sari, Novita; Mu’arif, Syamsul (Publika Citra Media, 2025)
This research aims to obtain empirical evidence regarding the influence of sales growth, fixed asset intensity and managerial ownership on tax avoidance. This type of research is quantitative research using associative methods. The population in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The sampling technique used in this research was obtained using the purposive sampling method. The total population in this study was 113 companies and 14 companies met the sample criteria and the sample after outliers was 10 companies. The analytical method used in this research is panel data regression analysis which is processed using the Eviews Version 12 application. The research results prove that: (1) Sales Growth has an effect on Tax Avoidance. (2) Fixed Asset Intensity has no effect on Tax Avoidance. (3) Managerial Ownership has no effect on Tax Avoidance. Sales Growth, Fixed Asset Intensity, and Managerial Ownership simultaneously influence Tax Avoidance.